Analisis Efektivitas Biofilter Pada Pengolahan Air Lindi di TPA Talangagung - Diena Widyastuti; Gettik Andri Purwanti; Didik Suprayitno (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2021)
Abstract Leachate from landfills, if left untreated, can lead to environmental pollution, especially if the leachate is discharged directly into the river. One way to reduce the environmental impact of seepage water is to treat the seepage water with a biofilter. The purpose of this study is to clarify the effect of leachate treatment with the use of biofilters. The method used in this study was to use laboratory-scale experimental methods. The biofilter used in this study was a combination of palm oil, sand, coconut shell charcoal, coconut fiber, gravel, and stone. The parameters measured in this study include pH, BOD, and COD. Based on the results of the studies conducted, biofilters have a significant impact on reducing the chemical content in the leachate. Biofilters have been shown to reduce the content of chemicals in osmotic water, so they do not pollute the environment, especially when it is discharged into rivers. The results showed that the COD and BOD values of the exudate were significantly reduced 6 weeks after treatment with the biofilter. The effectiveness of biofilms in reducing the chemical content in the leachate due to the presence of microorganisms growing in the biofilter layer is also based on the presence of biofilms formed by contact between the leachate and the biofilter.